Limites e possibilidades do programa nacional de alimentação escolar enquanto estratégia de promoção da segurança alimentar e nutricional no municipio de Macaíba/RN - Sousa, Emanuella Gracy Nunes Cadó (2013)
This dissertation aims to understand the importance of the National School Feeding as a strategy for ensuring the promotion of food and nutrition security in the municipality of Macaíba / RN, taking into account the implementation of the Law School Feeding, 11,947, 2009. The program was extended to all public basic education, youth and adults, in addition to ensuring that 30% of transfers from FNDE, were intended for the purchase of products from family farms. The survey was conducted with 160 students from public schools and farmers nesting Quilombo dos Palmares II, who produce on their land vegetables, fruits and cereals for their own consumption, for sale in local markets, in addition to providing for PNAE. The reciprocity between neighbors, such as mutual aid and sharing of common goods was noticeable in this group of farmers, since it was necessary to meet weekly deliveries of products to schools. As students, we applied a test of acceptability in two schools located in rural and in urban areas, to learn the opinion of ourselves in relation to school food consumed. It was concluded that to be most effective program in the region, there must be a better match in school menus, so that it can be attractive to students and to ensure greater use of fresh food, the main ingredient of same, practice of nutrition education in schools, to teach students the importance of food to health. In relation to local management, noted the need for adjustments bureaucratic as hiring staff for the departments, in order to be more agile in releasing payments to farmers, in addition to hiring assistants general services for schools, one Since the cooks exert dual role, the cooking while being responsible for cleaning the entire school environment. Government investments in the rural sector would be extremely valuable for farmers, since they need financial resources to purchase inputs, irrigation projects for gardens, availability of land for planting, transportation to facilitate the delivery of its products to schools and technical assistance more frequently